2014
DOI: 10.1101/gr.160010.113
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication and transcription programs respond to the same chromatin cues

Abstract: DNA replication is a dynamic process that occurs in a temporal order along each of the chromosomes. A consequence of the temporally coordinated activation of replication origins is the establishment of broad domains (>100 kb) that replicate either early or late in S phase. This partitioning of the genome into early and late replication domains is important for maintaining genome stability, gene dosage, and epigenetic inheritance; however, the molecular mechanisms that define and establish these domains are poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 70 publications
(78 reference statements)
12
80
0
Order By: Relevance
“…Our results are in excellent accord with similar studies in Drosophila that mapped ORC2 binding sites with respect to numerous chromatin properties and transcription factor binding sites (4)(5)(6). Although there are some differences in the analyses performed and in the molecular interpretation, the overall similarities of results and conclusions are striking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are in excellent accord with similar studies in Drosophila that mapped ORC2 binding sites with respect to numerous chromatin properties and transcription factor binding sites (4)(5)(6). Although there are some differences in the analyses performed and in the molecular interpretation, the overall similarities of results and conclusions are striking.…”
Section: Discussionsupporting
confidence: 88%
“…In the yeast Saccharomyces cerevisiae, ORC binds DNA in an ATP-dependent manner and recognizes a specific DNA sequence (3). In Drosophila, ORC localizes to regions of open chromatin with contributions from activating histone modifications, DNA sequence, DNA binding proteins, and nucleosome remodelers (4)(5)(6). In mammals, the mechanism(s) through which ORC is localized and establishes a functional origin remains unclear.…”
mentioning
confidence: 99%
“…The lower degree of compartmentalization and intermediate enrichment of transcription factors and histone marks in developmental domains may underlie their ability to switch between active and inactive epigenetic states more easily during the course of development. Indeed, a comparison of constitutive and developmental domains between two cell types in Drosophila revealed similar findings (Lubelsky et al 2014), and other studies have reported a similarity in nuclease sensitivity and origin density between developmental domains and constitutively late domains, regardless of their replication time (Besnard et al 2012;Takebayashi et al 2012).…”
Section: Wwwgenomeorgsupporting
confidence: 54%
“…Early replication is globally associated with active gene expression in all multicellular organisms (Schübeler et al 2002(Schübeler et al , 2004MacAlpine et al 2004;Woodfine et al 2004;Huvet et al 2007;Desprat et al 2009;Hiratani et al 2009;Schwaiger et al 2009;Maric and Prioleau 2010;Lubelsky et al 2014), and developmentally regulated changes in RT are generally coordinated with transcriptional competence (Zhou et al 2002;Hiratani et al 2008Hiratani et al , 2010Desprat et al 2009;Schultz et al 2010;Yue et al 2014). However, causal relationships between RT and gene expression remain a long-standing puzzle.…”
mentioning
confidence: 99%